2018
DOI: 10.1021/acsomega.8b02219
|View full text |Cite
|
Sign up to set email alerts
|

Selective Recovery of n-Butanol from Aqueous Solutions with Functionalized Poly(epoxide ionic liquid)-Based Polyurethane Membranes by Pervaporation

Abstract: In this study, hydroxyl-terminated polybutadiene–poly(epoxide ionic liquid)–poly(urethane urea) (HTPB-PEIL-PU) membranes, HTPB-PEIL1-PU and HTPB-PEIL2-PU, were prepared by the reaction of functionalized PEIL, poly(1-methylimidazole-3-methyl-ethyloxy)hexafluorophosphate or poly(1-methylimidazole-3-methyl-ethyloxy)bistrifluoromethanesulfonimidate, respectively, with HTPB using 4,4′-diphenylmethane diisocyanate (MDI) as the chain extender. The HTPB-PEIL-PU and HTPB membranes were investigated for the selective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Tang et al reported that hydroxyl-terminated polybutadiene-poly-(epoxide ionic liquid)-poly(urethane urea) (HTPB-PEIL-PU) membranes are capable of selectively recovering n-butanol from aqueous solutions. 168 PILs with ionic liquid species in their repeating units form a vast group of functional task-specific polymer materials. The application of PILs in SPME was first introduced by Anderson in 2008, by coating imidazolium-based PILs onto fibers.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Tang et al reported that hydroxyl-terminated polybutadiene-poly-(epoxide ionic liquid)-poly(urethane urea) (HTPB-PEIL-PU) membranes are capable of selectively recovering n-butanol from aqueous solutions. 168 PILs with ionic liquid species in their repeating units form a vast group of functional task-specific polymer materials. The application of PILs in SPME was first introduced by Anderson in 2008, by coating imidazolium-based PILs onto fibers.…”
Section: Applicationmentioning
confidence: 99%
“…Tang et al reported that hydroxyl-terminated polybutadiene–poly-(epoxide ionic liquid)–poly(urethane urea) (HTPB-PEIL-PU) membranes are capable of selectively recovering n -butanol from aqueous solutions. 168…”
Section: Applicationmentioning
confidence: 99%
“…An overview of various separation methods applied in downstream processing in a biorefinery has been reported in the literature. , Separation methods have been studied specifically for biobutanol recovery from fermentation broths based on flash fermentation, distillation, , gas stripping, membrane separation, extraction, and adsorption . Previous research on various membrane-based separation methods for 1-butanol recovery such as pervaporation, , membrane separation with gas stripping, and perstraction has led to the development of better membrane performance with reduced toxicity and energy consumption.…”
Section: Introductionmentioning
confidence: 99%